The process of Technology Leapfrogging: Case analysis of the national ICT infrastructure development journey of Azerbaijan. Issue 1 (February 2018) - Tan, Barney; Ng, Evelyn; Jiang, Junhui
Abstract: Technology Leapfrogging is one of the most cost efficient and effective ways for developing countries to attain an advanced state of ICT development and connectivity. And yet, despite its numerous benefits, there is currently little research on the process of Technology Leapfrogging. To address this knowledge gap, we conducted a case study of the national ICT infrastructure development journey of Azerbaijan, one of the top developing countries in the world in terms of ICT connectivity and development. With an in-depth exploration of how Azerbaijan charted the overall direction of ICT development, as well as the specific initiatives implemented in the areas of infrastructure development, e-government, information management and security, business and entrepreneurship, and research and education, a process model of Technology Leapfrogging was then inductively derived. More specifically, our study reveals that ICT development in Azerbaijan unfolded as a "stage-skipping" variant of Technology Leapfrogging that consists of four stages: (1) Psyching, (2) Planting, (3) Propelling and (4) Perpetuating. Analogous to the mechanics of a physical leapfrog, traversing the four stages enabled Azerbaijan to achieve an advanced state of ICT connectivity quickly and cost effectively in spite of its limited resources, which served to generate a variety of economic and social benefits for the country.